KAJIAN PEMBERIAN PUPUK GANDAPAN SUBLIMA DAN PUPUK MIKRO JAVA GREEN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI RAWIT (Capicum frutescens L.) - Suharso Suharso (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2017)
Abstract : Production of the Cayenne Pepper belongs to is still low compared to curly, chili farmers prefer to plant a chili pepper instead of curly and the average farmer who planted cayenne pepper in it has been still is traditional in nature. The purpose of this research is to know the influence of dose of fertilizer and fertilizer sublima micro java green towards the growth and production of the Cayenne Pepper (Capsicum frutescen L.). This research method using random design group (RAK) factorial which is composed of two factors, namely: treatment of factor 1 is a dose of fertilizer SUBLIMA (S), while the factor of 2 is a Micro fertilizer dosage (M). Factor 1: S1:5 kg/ha, S2:4 kg/ha, S3:3 kg/ha. Factor 2: MI: 5 kg/ha, M2:4 kg/ha, M3:3 kg/ha. Conclusion of this research is that the parameters of the vegetative growth occurred the interaction between fertilizer and fertilizer sublima micro java green on a high number of parameters of the plant, the leaves and the number of branches at the age of 14, 21, 28.35 days after planting. On the generative parameters occur an interaction between fertilizer and fertilizer sublima micro java green on fruit length parameters, number of pieces, and the weight of the fruit. . The best treatment combinations refractory the fertilizer with a dose of sublime awarding 4 kg/ha and fertilizer micro java green with a dose of 4 kg/ha.